Association between increase in vertical ground reaction force loading rate and pain level in women with patellofemoral pain after a patellofemoral joint loading protocol - Briani, Ronaldo Valdir [UNESP]; Pazzinatto, Marcella Ferraz [UNESP]; Waiteman, Marina Cabral [UNESP]; de Oliveira Silva, Danilo [UNESP]; de Azevedo, Fábio Mícolis [UNESP] (Elsevier, 2018)
Background: The etiology of patellofemoral pain (PFP) is thought to be the result of increased patellofemoral joint (PFJ) load and aberrant lower extremity mechanics, including altered vertical ground reaction forces (VGRF). However, few studies have investigated the association between an increase in pain and VGRF loading rates in the context of PFP. Thus, this study aimed to investigate the immediate effects of PFJ loading on pain and VGRF loading rate, and to see if there is a link between modification of both pain and VGRF loading rate during stair negotiation. Methods: Thirty-four women with PFP underwent VGRF analysis during stair negotiation under two conditions: with (condition 2) and without (condition 1) being previously submitted to a PFJ loading protocol in order to or not to exacerbate their knee pain, respectively. Results: The VGRF loading rates were significantly higher in condition 2 (Mean ± standard deviation (SD) = 4.0 ± 0.6 N/s) compared to condition 1 (Mean ± SD = 3.6 ± 0.5 N/s) during stair ascent and during stair descent (Mean ± SD: condition 1 = 6.3 ± 1.1 N/s; condition 2 = 7.0 ± 1.4 N/s). In addition, VGRF loading rates were higher during stair descent compared to stair ascent in both conditions. There were significant correlations between the increase in pain and VGRF loading rate during both tasks. Conclusion: There seemed to be an important relation between the increase in pain and VGRF loading rates in women with PFP. Based on these findings, interventions aimed at reducing VGRF loading rates are important in the context of PFP.
Keywords: Ground reaction forces; Loading rates; Patellofemoral pain; Stair negotiation